KEMAMPUAN MENULIS TEKS EKSPOSISI SISWA KELAS XI SMA TRI BHAKTI PEKANBARU - Stuti, Diana; Razak, Abdul; Sinaga, Mangatur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is entitled the ability to write exposition texts in class XI of SMA Tri Bhakti Pekanbaru. The purpose of this paper is to describe the level of ability to write exposition text of class XI students of Tri Bhakti Pekanbaru High School, and describe the differences in the ability to write exposition texts of class XI students of SMA Tri Bhakti Pekanbaru between sample groups. The data of this study are the results of the ability to write tests of the ability to write exposition texts in class XI of Tri Bhakti Pekanbaru High School which are divided into 2 classes as many as 46 students with a sample of 41 students. The results of the study after testing the chi square test of one sample, the ability to write exposition text of class XI students of Tri Bhakti Pekanbaru High School is equal to the comparative value of 75. The ability to write exposition text of class XI students of SMA Tri Bhakti Pekanbaru is moderate. Then, testing was carried out using the Mann Whitney test, to determine the difference in ability to write exposition texts in class XI of SMA Tri Bhakti Pekanbaru between sample groups. The result is no difference in the ability to write exposition text between sample groups.Keywords: Abilities, exposition text